THE TRANSHUMANIS’M PERSPECTIVE: CONCEPTS OF THE POSTHUMAN - Kiselyova, Tetyana (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2023)
Introduction. Posthuman concepts raise many ethical, philosophical and social questions. Such as fair access to such technologies, preservation of our humanity, interaction of new forms of posthuman society and culture, and others. These questions require investigation and critical reflection if we are to influence our posthuman future. The aim of the article is an analysis of transhumanism as a metacultural attitude that affects modern humanity and shapes its future prospects. Special attention is focused on ideas and concepts of transhumanism influence the formation of the concept of the posthuman, and how this process can change our understanding of human existence. We aim to indicate the essence of the concept of the posthuman in the context of transhumanism and the technological and socio-cultural changes necessary for its emergence and the consequences and ethical challenges along the way. Research methodology is a complex of philosophical and general scientific methods. The article also uses sociocultural, systemic and synergistic approaches. Research results. Philosophers in their research emphasize the need to develop careful cultural and political strategies to control the development of the posthuman and minimize potential negative risks. First, technological progress itself must be regulated, because any interference in human nature must not lead to negative consequences. Secondly, it is important that society is informed about how technological progress can affect the future. Thirdly, it is important to invest in scientific research in order to gradually introduce technological advances into our lives and start a deliberate path to the posthuman now. Conclusions. The posthuman is a possible future for humanity. And the evolution of man to post-man began yesterday. It is important that we actively manage this process, using regulation, ethical standards, scientific research and social dialogue to ensure that a posthuman future is in our collective interest and a common human value